MEWUJUDKAN PENDIDIKAN BERKUALITAS DAN PEMBANGUNAN MASYARAKAT YANG INKLUSIF UNTUK SDGS 2030 BERBASIS TEKNOLOGI MELALUI LITERASI DIGITAL - Septiani, Astri; Sumitasen, Jethan; Rachman, Ichsan Fauzi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
This research discusses the importance of digital literacy and efforts to improve quality education and inclusive community development for SDGs 2030. The aim of this research is to understand the important role of digital literacy in achieving sustainable development goals in community development and education. The research method used is the literature review method by collecting and combining other sources that are relevant to the research topic to draw a conclusion. The results of this research show efforts to achieve SDGs in the realm of education and community development. Digital literacy is very important in cultivating the intellectual and intelligent character of a nation, thereby enabling individuals to make choices and access accurate information. In increasing digital literacy, the use of technology can be a means to develop technological skills so that individuals become capable and master technology well. By strengthening digital literacy, society can be better prepared to face the future by developing creativity, innovation and adaptability in overcoming various challenges